Lifestyle in Controlling Hypertension and Its Associated Factors - Malau, Ana Silvia; Limbong, Adelya Octavia; Lopo, Ferawati; Pakpahan, Martina; Cicilia, Sarah Lidya (Universitas Malahayati, 2024)
ABSTRACT Hypertension is a silent killer that can result in stroke, kidney failure, heart failure, chronic disability, and death. An unhealthy lifestyle becomes a significant risk factor for hypertension. Lifestyle modifications such as salt limitation, stop smoking, decreased alcohol intake, stress management, and weight control are crucial in controlling hypertension. The Study aims to determine the lifestyle of hypertensive patients in managing hypertension and the factors related to it. A cross-sectional study was conducted. Purposive sampling yielded a sample of 30 persons. Patients having a history of hypertension, using hypertension medication, and aged 30-45 years were eligible. An online questionnaire that had passed validity and reliability tests was used to collect data. Univariate and bivariate analyses are used. The study findings revealed that 43.3% of respondents have a bad lifestyle and 56.7% have a healthy lifestyle when it comes to regulating hypertension. The majority of respondents were fe2male (63.3%), worked (96.7%), married (83.3%), had a moderate education (70%), less than 43 years old (60%), had normal body weight (60%), had hypertension for less than 5 years (90%), and had uncontrolled blood pressure (66.7%). Furthermore, education level and body weight were found to be associated with lifestyle in controlling hypertension, although gender, age, working status, marital status, duration of hypertension, and blood pressure were not. Lifestyle modifications can be emphasized in hypertension control programs by raising hypertensive patients' awareness. Keywords: Lifestyle, Hypertension, Risk Factors